2021
DOI: 10.1186/s13034-021-00424-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parental divorce versus separation due to migration on mental health and self-injury of Chinese children: a cross sectional survey

Abstract: Background There has been an increasing prevalence of parental separation in China due to divorce or migration for work in recent decades. However, few studies have compared the impacts of these two types of separation on children’s mental health. This study aimed to investigate how parental divorce and parental migration impact children’s mental health and self-injurious thoughts and behaviors (SITB), while considering positive factors, including parent-adolescent communication and psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 56 publications
0
5
0
2
Order By: Relevance
“…Therefore, parental divorce would be a potential moderator between negative life events and depression. In addition, divorce-related stigma still exists in most rural areas in China 36 . Not only cross-sectional studies showed that there was a relationship between stigma and low self-esteem, but also a longitudinal study indicated that stigma played a casual role in reducing the self-esteem level 37 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, parental divorce would be a potential moderator between negative life events and depression. In addition, divorce-related stigma still exists in most rural areas in China 36 . Not only cross-sectional studies showed that there was a relationship between stigma and low self-esteem, but also a longitudinal study indicated that stigma played a casual role in reducing the self-esteem level 37 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adolescents with pathological family relationships and disharmonious relationships with their parents have a higher risk of self-harm ( 23 ). Furthermore, experiencing adverse life events (parental abuse or neglect) in childhood ( 24 ), parental divorce ( 25 ), family death ( 26 ), and witnessing parental violence ( 27 ) have all been associated with NSSI behaviors in adolescents. Notably, improving family relationships may reduce NSSI in later childhood who experience adverse life events in childhood.…”
Section: Introductionmentioning
confidence: 99%
“…According to some studies, children of parents who continue post divorce dating behavior, live together and change partners frequently have behavioral problems and their well-being is negatively affected. According to some studies, these relationship styles have been found to negatively affect emotional-secure attachment styles in children (Wang et al, 2021). While developing a harmonious relationship with the mother's post divorce dating partner positively affects the child's development, termination of the partnership relationship may lead to an increase in internalizing and externalizing behaviors and stress levels in children (Langlais et al, 2018).…”
Section: Psychological Problemsmentioning
confidence: 99%